PEMBERDAYAAN MASYARAKAT MELALUI PENDIDIKANPERENCANAAN DAN PENGELOLAAN KEUANGAN DAN INVESTASIBAGI UMKM DALAM RANGKA PENGEMBANGAN USAHA DANPENINGKATAN KUALITAS HIDUP KELUARGA - Suryanto, Dede; Dwi Liestiawati, Fibria Indriati; Suwaryono, Ixora Lundia; Soeling, Pantius Drahen (UI Scholars Hub, 2015)
Community Engamenet Program gives the skill of planning and financing education for Small Medium Entreprises (SME), how they make business plan begin budgeting, raising the fund, create financial statement, buseiness development and investing to enhance their wealth of family. This program delivered to 30 SME of Assosiation of Depok Creative Industries (AIKD). Some activities delivered are training and business assistance. The aims of program point out some changes before and after program impelementation. The SME have positive behavior in financing. The success indicators are the SME have financial statement of entrepreises and their family. In otherwise they they can make financial decision wisdom to depelove their entreprises. Hopelly, this program be allowed to to their business needs and can continue and consisten.